Students' Competence in Micro-Teaching Course at English Department - Nursia, Sitti; Alimin, Alimin; Rohmana, Rohmana (Journal of Teaching English, 2019)
This study aims at determining students’ competence in Micro-Teaching course at English Department. The researcher exclusively focused on analyzing the seven skills they are: opening and closing the lesson, explaining skill, questioning skill, reinforcement, providing variation, classroom management and guiding small group discussion. The subject of the study was students at English Department who were taking Micro-Teaching course. The totals of the subject were 30 students. The researcher employed descriptive qualitative design with observation, video and assessment rubric. The result show differently in which students’ mastery level in opening and closing the lesson is good with the average score 72%, explaining skill is very good with the percentage of average score 81%, questioning skill is very bad with the percentage of average score 59%, reinforcement is very good with the percentage of average score 88%, providing variation is very bad with the percentage of average score 49%, classroom management is bad with the percentage of average score 55%, and the last guiding small group discussion is very bad with the percentage of average score 26%. Besides, it also portrayed that the most mastered skills among all skill is reinforcement and skill the most lack is guiding small group discussion.